Production Scheduling Analysis to Minimize Makespan with Nawaz Enscore Ham Method at Maros Futry Bakery and Cake Shop - Uyun, Dzahratul; Lamatinulu; Hafid, Muhammad Fachri (Journal of Sustainability Industrial Engineering and Management System, 2023)
This study aims to regulate the production schedule to reduce product makespan caused by increasing demand. This study using the Nawaz Enscore Ham method to minimize makespan on the production schedule at the Maros Futry Bakery and Cake Shop is very relevant and important. The results of this study are obtained from job sequences from the NEH method are J3-J2-J1 with a makespan time of 2.72 hours Based on the analysis and discussion, the conclusion of this study is the sequence of work in the futry bakery and cake shop obtained by the nawaz enscore ham method, namely J3-J2-J1 or on the product bolu mabel – bolu rempah – maros bread obtained during makespan which is 9827.84 seconds or 163.79 minutes or equal to 2.72 hours. So that it can reduce the buildup of demand with an increasingly fast time compared to the company's makespan time, which is 7.18 hours.